The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.25165/j.ijabe.20211405.6265
|View full text |Cite
|
Sign up to set email alerts
|

Effects of multi-sequence combination forces on creep characteristics of bales during wheat harvesting

Abstract: During the baling operation, the wheat stalks are subjected to various mechanisms in the baler and the main form is compression. After the wheat stem is forced by a combination of the threshing cylinder, it needs to be formed under the action of straw baler and meet transport requirements. This paper mainly studies the properties of wheat stalks when baling, and proposes the application of the creep after-effect theory during the baling process. The tension-compression tester was used to perform a 50 mm stalk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The deformation curve in the holding stage is close to horizontal,and this theory is in line with the creep law of certain density silage. Therefore,the four-component Burgers model was also chosen to analyse the creep characteristics of the crushed cane tail leaves during the holding pressure stage (Tang et al 2021). The relationship equation for the variation of creep history of crushed SEL during holding pressure stage is: Using mathematical statistical analysis software SPSS to fit and regression analysis of the creep curve of the holding pressure stage of crushed SEL under different influencing factors, we obtained the creep characteristic parameters under the conditions of different influencing factors.…”
Section: Selection Of Creep Model For Holding Pressure Stagementioning
confidence: 99%
“…The deformation curve in the holding stage is close to horizontal,and this theory is in line with the creep law of certain density silage. Therefore,the four-component Burgers model was also chosen to analyse the creep characteristics of the crushed cane tail leaves during the holding pressure stage (Tang et al 2021). The relationship equation for the variation of creep history of crushed SEL during holding pressure stage is: Using mathematical statistical analysis software SPSS to fit and regression analysis of the creep curve of the holding pressure stage of crushed SEL under different influencing factors, we obtained the creep characteristic parameters under the conditions of different influencing factors.…”
Section: Selection Of Creep Model For Holding Pressure Stagementioning
confidence: 99%
“…Different from wheat, rice, rape, and soybean, garlic (Allium sativum L.) is a typical vegetable and herb of the genus Allium in the family Liliaceae [15] . According to its morphology and purpose, it can be divided into two types, namely bolt garlic and non-bolt garlic, among which, non-bolt garlic maturing in different periods is a widely cultivated variety currently.…”
Section: Characteristics Of Garlic Plantsmentioning
confidence: 99%
“…However, the density of the existing harvesting and packaging machine could reach 199-240 kg/m 3 [9]. Research results on other agricultural materials are more abundant, and the theory is more well established [10][11][12]. Xiao et al [13] outlined the creep properties of rice seedlings by using the Burgers model and showed that different load levels have an influence on creep parameters.…”
Section: Introductionmentioning
confidence: 99%